Campus life adaptation and dietary patterns among first-year health science students in Indonesia: a cross-sectional study - Rukmoyo Endrawan; Daning Widi Istianti (International Journal of Public Health Science (IJPHS), 2026)
Adaptation to campus life can be a challenging process for new students and may influence health-related behaviors, including dietary patterns. A preliminary study involving five first-year students showed that they experienced difficulties managing their dietary patterns during their first semester. However, evidence regarding the relationship between adaptation to campus life and dietary patterns among first-year health students in Indonesia remains limited. This study employed a correlational design with a cross-sectional approach and involved 36 respondents. Data were collected using the Student Adaptation to College Questionnaire (SACQ) and the Adolescent Food Habits Checklist (AFHC) and were analyzed using Spearman’s rho correlation test. Most respondents were female (81%), and 69% were in the adolescent age group. The majority of respondents demonstrated a moderate level of adaptation to campus life (92%) and reported healthy dietary patterns (92%). A significant positive correlation was found between adaptation to campus life and dietary patterns (p < 0.001, r = 0.734), indicating that students with higher levels of adaptation tended to have healthier dietary patterns. These findings suggest that institutions should provide campus-based health promotion programs, including student services, counseling, stress management programs, and dietary education.